A Comparative Study on Corporate Social Responsibility between Two Selected Companies in India - Sankar Paul (New Ideas Concerning Arts and Social Studies Vol. 2, 2025)
Corporate Social Responsibility defies the company’s moral and social responsibility to the stakeholders, i.e. environment, people, society and community development at large. This study aims to exhibit the impact of the CSR activities of selected companies on consumer perception. The second part of the study highlights the amount of CSR expenditure spent by Dabur India Ltd. and Marico Ltd for the financial years 2018-19 to 2022-23, covering different areas like promotion of preventive healthcare, environmental sustainability, promotion of education and community development. Regarding CSR expenditure, Dabur India Ltd. spent more funds than Marico Ltd for the financial years 2018-19 to 2022-23. The findings revealed that Dabur India Ltd. mainly focus on contributing CSR funds in promoting preventive healthcare and promoting education, and Marico Ltd. contributes more funds to environmental sustainability. Both companies spent more funds during the financial years 2018-19 to 2022-23 than the prescribed limit of CSR expenditure. Regarding consumers’ perception, the results also showed that male respondents are more aware of the CSR activities than female respondents. Both neglected the CSR areas like disaster management measures, contribution towards the protection of the National heritage and benefits of armed force veterans. Both companies must disclose the CSR reporting in their Annual Reports for the sake of stakeholders and investors at large.